(untitled) (Research, Society and Development, 2021)
Brazilian Higher Education has expanded strongly in recent years and the adoption of public policies for student access and permanence has brought to higher education institutions a high number of students from public schools and in adverse socioeconomic conditions. This Article is the result of a bibliographic investigation on education as a social right and the historical framework of Quotas in Brazil and its legislation, as well as the implementation at the Federal Institute of Education, Science and Technology of Santa Catarina.